A study of the Shk40 compact galaxy group - Karapetyan, E. L.
A compact group represents a specialized type of galaxy system where member galaxies are separated by distances roughly equivalent to the size of galaxies themselves. The intense interactions among these galaxies make compact groups ideal laboratories for investigating the environmental impacts on galaxy evolution. In this study, we aim to investigate the Shk40 cluster from the Shahbazian catalog of compact groups of galaxies.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture